Analisis Pengaruh Family Ownership dan Ukuran Perusahaan terhadap Manajemen Laba pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 (Jurnal Kendali Akuntansi, 2025)
This study aims to analyze the effect of family ownership and firm size on earnings management practices in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Earnings management has become a crucial concern as it may harm stakeholders due to financial statements that do not reflect the actual financial condition. Family ownership remains dominant in the ownership structure of companies in Indonesia, potentially influencing corporate accounting decisions, including earnings management practices. This research applies a quantitative method using secondary data from annual financial reports of manufacturing companies obtained from the official IDX website. The data analysis technique employed is multiple linear regression with the assistance of SPSS software. The results show that family ownership has a significant effect on earnings management, while firm size has no significant effect. Meanwhile, family ownership and firm size simultaneously have a significant effect on earnings management. These findings are expected to serve as valuable input for investors, regulators, and companies in enhancing financial reporting transparency.